DETERMINATION OF WATER-SOLUBLE VITAMINS CONTENT IN YOGURT USING THE HPLC METHOD - Furqatjon Begmatov; Barnokhon Sattarova (Academia One Publishing, 2025)
In this study, a high-performance liquid chromatography (HPLC) method based on the HPLC technique was developed for the determination of water-soluble vitamins (B₁, B₂, B₃, B₆, B₉, B₁₂, PP, and C) in yogurt. Standard vitamin solutions were prepared in 0.1 N hydrochloric acid (HCl) and 0.025% sodium hydroxide (NaOH) solutions and analyzed using a Shimadzu LC40 Nexera Lite system equipped with a Shim-pack GIST C18 column under gradient elution conditions. The yogurt sample extract was prepared by ultrasonic-assisted extraction at 60°C for 20 minutes with 0.1 N HCl, followed by filtration through a 0.22 µm syringe filter prior to analysis
Keywords: yogurt; water-soluble vitamins